2016
DOI: 10.1126/science.aaf1175
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recordings by directed CRISPR spacer acquisition

Abstract: The ability to write a stable record of identified molecular events into a specific genomic locus would enable the examination of long cellular histories and have many applications, ranging from developmental biology to synthetic devices. We show that the type I-E CRISPR-Cas system of E. coli can mediate acquisition of defined pieces of synthetic DNA. We harnessed this feature to generate records of specific DNA sequences into a population of bacterial genomes. We then applied directed evolution to alter the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
211
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(220 citation statements)
references
References 46 publications
7
211
1
1
Order By: Relevance
“…Protospacer electroporations were performed as previously described 8 . Briefly, after overnight outgrowth from a single colony, Cas1+2 were induced in a 3 ml dilution of the culture (containing 80ul of the overnight), and grown at 37C for 2 hours (L-arabinose 0.2% w/w, Sigma-Aldrich; isopropyl-beta-D-thiogalactopyranoside 1mM, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Protospacer electroporations were performed as previously described 8 . Briefly, after overnight outgrowth from a single colony, Cas1+2 were induced in a 3 ml dilution of the culture (containing 80ul of the overnight), and grown at 37C for 2 hours (L-arabinose 0.2% w/w, Sigma-Aldrich; isopropyl-beta-D-thiogalactopyranoside 1mM, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Using the Cas1-Cas2 integrase, the CRISPR-Cas microbial immune system stores the nucleotide content of invading viruses to confer adaptive immunity 7 . Harnessed, this system has the potential to write arbitrary information into the genome 8 . Here, we use the CRISPR-Cas system to encode images and a short movie into the genomes of a population of living bacteria.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Some work has shown that cells containing CRISPRCas machinery could serve as a recording device of sorts, cataloguing DNA and RNA sequences that they have encountered 3 . This might allow researchers to track a cell's gene expression or exposure to environmental chemicals over time.…”
Section: How Does It Work?mentioning
confidence: 99%